COMMON GARDEN OF SEAGRASSES Halodule uninervis (Forsskål) Aschershon AND Halodule pinifolia (Miki) den Hartog - Wagey, Billy Theodorus (Sam Ratulangi University, 2012)
A simple culture system ‘common garden’ has been set up in Institute of Environmental and Marine Science (IEMS) Dumaguete City Philippines (N 09° 19' 52.8